2019
DOI: 10.47203/ijch.2019.v31i03.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight obesity among M.B.B.S. students

Abstract: Background: Prevalence of overweight-obesity is rising in India. Medical Professionals are vulnerable to overweight-obesity because of the sedentary lifestyle which is frequently adopted due to massive work burden. Aim & Objective: To assess prevalence of overweight-obesity and associated factors among MBBS students in a medical institute in north-Indian state of Uttarakhand. Settings and Design: Descriptive cross-sectional study Methods and Material: This study was conducted among 310 M.B.B.S. students at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…Earlier studies from Southern central and parts of India have shown prevalence of overweight-obese among medical students ranging from 9.4% to 37.5%. 7,8,12,13 The possible reasons for prevalence of overweight-obesity higher in study population of the present study may be (i) dietary habits, (ii) physical activity, and (iii) sociodemographic profile.…”
Section: Discussionmentioning
confidence: 70%
“…Earlier studies from Southern central and parts of India have shown prevalence of overweight-obese among medical students ranging from 9.4% to 37.5%. 7,8,12,13 The possible reasons for prevalence of overweight-obesity higher in study population of the present study may be (i) dietary habits, (ii) physical activity, and (iii) sociodemographic profile.…”
Section: Discussionmentioning
confidence: 70%
“…1 The prevalence of overweight in Dehradun, India is 21% which was slightly lower than in our study but similar to another study done in Malaysia. 4,5 The prevalence of overweight was higher in male students than females in Malaysia but higher in females than males study done in India. 5,4 Another study done in India, Pakistan, and Pune India showed a 10%, 6 14.7%, 7 and 13% 8 prevalence of overweight which was lower than in our study and a higher prevalence seen in male students than in females but higher in the female study done in Pune India.…”
Section: Discussionmentioning
confidence: 90%
“…4,5 The prevalence of overweight was higher in male students than females in Malaysia but higher in females than males study done in India. 5,4 Another study done in India, Pakistan, and Pune India showed a 10%, 6 14.7%, 7 and 13% 8 prevalence of overweight which was lower than in our study and a higher prevalence seen in male students than in females but higher in the female study done in Pune India. [6][7][8] A similar study done in Jammu India which was found around 19% prevalence of overweight which was slightly lower than in our study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations